Toxoplasmosis Titers and past Suicide Attempts Among Older Adolescents Initiating SSRI Treatment. Issue 4 (1st October 2016) - Coryell, William; Yolken, Robert; Butcher, Brandon; Burns, Trudy; Dindo, Lilian; Schlechte, Janet; Calarge, Chadi
Abstract : Latent infection with toxoplasmosis is a prevalent condition that has been linked in animal studies to high-risk behaviors, and in humans, to suicide and suicide attempts. This analysis investigated a relationship between suicide attempt history and toxoplasmosis titers in a group of older adolescents who had recently begun treatment with an SSRI. Of 108 participants, 17 (15.7 %) had a lifetime history of at least one suicide attempt. All were given structured and unstructured diagnostic interviews and provided blood samples. Two individuals (11.9%) with a past suicide attempt, and two (2.1%) without this history, had toxoplasmosis titers ≥ 10 IU/ml (p = 0.166). Those with a past suicide attempt had mean toxoplasmosis titers that were significantly different (p = 0.018) from those of patients who lacked this history. An ROC analysis suggested a lower optimal threshold for distinguishing patients with and without suicide attempts (3.6 IU/ml) than that customarily used to identify seropositivity. Toxoplasmosis titers may quantify a proneness to suicidal behavior in younger individuals being treated with antidepressants.